Analisis Spasial Perkawinan Usia Anak pada Kabupaten/Kota di Pulau Sulawesi Tahun 2022 - Yahya, Muhammad Gozali; Sitorus, Jeffry Raja Hamonangan (Politeknik Statistika STIS, 2024)
Indonesia has an alarming rate of child marriage. The acceleration of the elimination of child marriage cannot be delayed because it can threaten the future of the younger generation. Child marriage is influenced by regional factors as evidenced by the districts/cities on Sulawesi Island having a percentage of child marriage above the national rate. The purpose of this study is to determine the general description of the percentage of child marriage and factors that are thought to influence child marriage in districts / cities on Sulawesi Island in 2022. The research method used is Spatial Autoregressive (SAR). The results of the analysis show that the percentage of child marriage in districts/cities on Sulawesi Island has a spatial pattern. Then the variables of Average Years of Schooling (RLS) of women, Life Expectancy (UHH), average Family Welfare Empowerment (PKK) per village, proportion of villages that have Elementary School (SD) and Junior High School (SMP), percentage of rural areas, and adjusted expenditure per capita of women have a significant effect on the percentage of child marriage in districts/cities in Sulawesi Island.